Differences in suicidal behaviors between self‐employed and standardly employed workers. Issue 12 (23rd September 2019) - Min, Jin‐Young; Kim, HyeJin; Park, Shin‐Goo; Hwang, Sang Hee; Min, Kyoug‐Bok
Abstract: Background: Although self‐employed persons have greater autonomy, schedule flexibility, and control over their work than employees, they may be among the most vulnerable workers due to the lack of social benefits and protection from labor law and regulations. We compared suicidal behaviors between the self‐employed and standardly employed workers. Methods: This study used the 2008 Korean Community Health Survey data and included a total of 64 802 working population. Self‐employed persons were classified into "small business self‐employed persons" with zero to four employees and "middle to large business" with more than five employees. The outcomes were suicidal ideation and suicide attempts. Results: Of the 64 802 participants, 40 422 were engaged in standard employment, and 24 380 were self‐employed, with almost 90% ( n = 21 970) being engaged in small businesses. Persons self‐employed, compared with standard workers, were more likely to report suicidal ideation in both small (odds ratio [OR] = 1.25; 95% confidence interval [CI], 1.15‐1.35) and middle to large businesses (OR = 1.32; 95% CI, 1.09‐1.61). On the other hand, the likelihood for suicide attempt was only significant in persons self‐employed in small businesses (OR = 1.67; 95% CI, 1.11‐2.45). Conclusion: Self‐employed persons were associated with greater odds of reporting suicidal behaviors than workers with standard employment. Among the self‐employed, small business owners were particularly vulnerable to suicide attempts.